Male fairy-wrens produce and maintain vibrant breeding colors irrespective of individual quality. (22nd December 2020) - McQueen, Alexandra; Delhey, Kaspar; Barzan, Flavia R; Naimo, Annalise C; Peters, Anne
Abstract: Conspicuous colors may signal individual quality if high-quality individuals produce more elaborate colors or have a greater capacity to invest in color maintenance. We investigate these hypotheses using repeated within-individual observations and experimentally induced color production in a wild bird, the superb fairy-wren ( Malurus cyaneus ). Male superb fairy-wrens undergo an annual molt from brown, nonbreeding plumage to an ultraviolet-blue and black breeding plumage. Color maintenance is especially relevant for this species because structural, ultraviolet-blue plumage colors are particularly susceptible to fading. Further, only the most sexually attractive males molt to breeding plumage early (before spring) and thereby keep their colors for an extended time before the breeding season. Our results show that (i) sexually attractive, early-molting males do not have higher quality breeding colors and (ii) breeding colors are not impacted by experimentally inducing males to molt early and while in low body condition. We found that (iii) breeding colors do not fade but remain consistent or become more saturated within individuals over time. Despite this, (iv) males do not spend more time preening while in breeding plumage. Instead, males keep their colors in pristine condition by re-molting parts of their breeding plumage throughout the breeding season, suggesting an alternative, potential cost of maintaining ornamental colors. We conclude that variation in structural breeding colors is unlikely to indicate individual quality in superb fairy-wrens. Abstract : All male superb fairy-wrens can produce vibrantly colored feathers, even when forced to do so with few resources and in challenging conditions. This is surprising, as it is expected that the most vibrant colors are only achieved by high-quality, resource-rich males. Males maintain ultraviolet-blue and black colors without extra preening, by 'retouching' their plumage with re-grown feathers. Our results show that all male fairy-wrens invest in attractive colors, irrespective of their quality.